Selective inhibition of purified human phosphodiesterase 4A expressed in yeast cell GL62 by ciclamilast, piclamilast, and rolipram - CHEN Jun-chun; CHEN Ji-qiang; XIE Qiang-min; ZHU Yi-liang (Acta Pharmacologica Sinica; Vol 25, No 9 (September 2004): Acta Pharmacologica Sinica, 2016)
AIM: To improve the specific activity of human phosphodiesterase 4A (PDE4A) expressed in yeast cell GL62 and investigate the effects of selective phosphodiesterase 4 (PDE4) inhibitors (ciclamilast, piclamilast, and rolipram), selective phosphodiesterase 5 (PDE5) inhibitor zaprinast, and cyclooxygenase (COX) inhibitors (aspirin, indomethacin) on human PDE4A activity expressed in yeast cell GL62. METHODS: Human PDE4A was expressed in yeast cell GL62 after CuSO4 induction and the specific activity of human PDE4A was improved by ammonium sulfate fractionation, DEAE Sephadex A-50 chromatography, and Sephadex G-100 chromatography. The activity of PDE4A was measured by high performance liquid chromatography (HPLC). RESULTS: Induced PDE4A activity expressed in crude yeast cell GL62 supernatant and pellet was (340+/-21) nmol/g/min and (250+/-25) nmol/g/min respectively. The specific activity of recombinant PDE4A in supernatant was improved 6.4 fold. Ciclamilast, piclamilast, and rolipram could inhibit PDE4A activity. The IC50 values (95 % confidence limits) of ciclamilast, piclamilast, and rolipram were 1.27 (0.84-1.91), 66.4 (33.3-132.2), and 3.73 (2.51-5.53) micromol/L respectively. Zaprinast, aspirin, and indomethacin had no obvious inhibitory effect on PDE4A activity. CONCLUSION: The specific activity of PDE4A expressed in yeast cell GL62 can be improved by ammonium sulfate fractionation, DEAE Sephadex A-50 chromatography, and Sephadex G-100 chromatography. Ciclamilast, piclamilast, and rolipram can inhibit PDE4A activity while zaprinast, aspirin, and indomethacin have no obvious inhibitory effect on PDE4A activity. Human PDE4A expressed in GL62 might be useful in the research and screening of new selective PDE4 inhibitors.